Falar apaisanado: uma forma de designar as línguas na fronteira - Alvarez, Isaphi Marlene Jardin (2009)
The research was developed in Linguistics Studies, in the research line: Language, Subject and History and contemplates Enunciation theories guiding to a reflection about the designation of the other s language, it means, how to give a name to the language of the other which is already named, taking into consideration the border enunciation space. In this sense, Enunciation Space concepts were approached as constitutive of a relation between languages or, more specifically, to analyze the different ways of designating the languages spoken in border zones through oral utterances produced by border speakers. This research became effective since a bibliographical review was made, giving emphasis to the theoretical support which was adopted in this work. The corpus of this research was composed by parts of oral utterances produced by border speakers. From this perspective, it is interesting to think that this speaker-language relation refers to the issue concerning the subject in language, the speaker which expresses himself while enunciating, thus the implications or effects this announcer s enunciation causes when he takes property of the language, making it work and have meaning. One hypothesis is that the subject which uses Border Languages expresses them in different ways, making them to have meaning, while talking about the other s language. Thus, the enunciation space configures in this relation between languages and speakers, which also constitutes an interlanguages space. Hence, there is the choice of a language of enunciation or a language for enunciation. It is this choice, always regulated by the hierarchy status of languages, that defines enunciation as the subject s political place. Looking to the function and the meaning of language, it is also evidenced the current signification, with a past of memories established by temporality. Such temporality permits languages to build sense while interacting in the same enunciative space. Once it is a study area in which the relations between languages have been considered, it is relevant to have a research proposal concerning the designation given by the speakers themselves in relation to Portuguese and Spanish and the languages that are (or aren t) practiced, taking into consideration the border enunciation space.